KESANGKILAN PASAR HASIL PERIKANAN DI KAWASAN PESISIR - Muchtar Ahmad (UIR Press, 2013)
The state of fishery marketing concerning its marketing system, price at various levels, and marketing efficiency in the coastal area of Batubara regency are reported. Data and information based on survey, which was conducted on fishers, who fishing in the coastal waters of the regency. There are two basic flows fish commodities through different functional marketing systems from the point of fishers as producers to consumers. First, marketing system of the fish from artisanal fishers was used to the collecting fish traders. Since the traders are persisting in many points of marketing, the channel is rather length. Second, fish marketing through private fish landing place of the fish caught by own boat or special tied fishers to the landing places. The flow chain of the system is shorter than the former, low marketing margin, so that the marketing efficiency is rather high. The sold price and marketing margin seemingly differs at each institution point of marketing system. It determined by timing and the length of transportation time, economy, accuracy, the length of marketing chain, and the price at each point of the chain, which the handling fish flows determine of the efficiency of the distribution channel. In order to improve marketing efficiency and artisanal fisher’s income from the fish marketing by receiving of the fair fish price, it is necessary to develop open market by means of functionalized government established landing places. Hence, the length of marketing chain is shorter, and followed by supporting of functionalized fishers cooperative that able to manage the landing places. So that many marketing institutions of the fish traders are successed by in the efficient marketing system.